2000
DOI: 10.1029/1999je001169
|View full text |Cite
|
Sign up to set email alerts
|

Determination of habitable zones in extrasolar planetary systems: Where are Gaia's sisters?

Abstract: Abstract. A general modeling scheme for assessing the suitability for life of extrasolar planets is presented. The scheme focuses on the identification of the "habitable zone" in main sequence star planetary systems accommodating Earth-like components. Our definition of habitability is based on the long-term possibility of photosynthetic biomass production under geodynamic conditions. Therefore all the pertinent astrophysical, climatological, biogeochemical, and geodynamic processes involved in the generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 27 publications
(10 reference statements)
2
59
0
2
Order By: Relevance
“…Other more general criteria to understand the optimal position of the HZ was proposed by Franck et al (2000aFranck et al ( , 2000b. Based on the global carbon cycle as mediated by life and driven by increasing solar luminosity and plate tectonics, they estimated the biogeophysical domain supporting a photosynthesis-based ecosphere during planetary history and future.…”
Section: Introductionmentioning
confidence: 99%
“…Other more general criteria to understand the optimal position of the HZ was proposed by Franck et al (2000aFranck et al ( , 2000b. Based on the global carbon cycle as mediated by life and driven by increasing solar luminosity and plate tectonics, they estimated the biogeophysical domain supporting a photosynthesis-based ecosphere during planetary history and future.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al (2005Jones et al ( , 2006 applied this framework to known exoplanetary systems to evaluate the possibility of habitable "Earths". Stellar evolutionary aspects are also relevant to the future of life on Earth, as discussed by, e.g., Sackmann et al (1993) and Schröder & Smith (2008), although the impact of geodynamic processes appears to be dominant for setting the time limit of terrestrial habitability (Franck et al 2000b). Customary simulations about the role of stellar evolution on circumstellar habitability typically invoke the framework of the climatic habitable zone (Kasting et al 1993;Selsis et al 2007).…”
Section: 3mentioning
confidence: 99%
“…Note that concerning Earth-mass planets, a detailed study of geodynamic habitability based on the pHZ was previously presented by Franck et al (2000b). They found that Earth will be rendered uninhabitable after 6.5 Gyr as a result of plate tectonics, notably the growth of the continental area (enhanced loss of atmospheric CO 2 by the increased weathering surface) and the dwindling spreading rate (diminishing CO 2 output from the solid Earth).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kasting et al (1993) emphasized that the habitability of an exoplanet depends on the properties of the host star. Several authors have considered how a planet's climate and climatic habitability depend on the properties of the planet, as well (Williams & Kasting 1997;Franck et al 2000aFranck et al , 2000bWilliams & Pollard 2002;Gaidos et al 2005;von Bloh et al 2007von Bloh et al , 2008; Selsis et al 2007;Dobrovolskis 2007Dobrovolskis , 2009Spiegel et al 2008Spiegel et al , 2009). In particular, two recent works have focused on the climatic effect of orbital eccentricity.…”
Section: Introductionmentioning
confidence: 99%